Deep Insight into the Pinch Effect in a Tundish with Channel‐Type Induction Heater. Issue 9 (29th May 2022) - Zhang, Han; Lei, Hong; Ding, Changyou; Chen, Shifu; Niu, Hong; Yang, Bin
Abstract : Tundish with channel‐type induction heater plays an important role in the continuous casting of high‐quality steel. Electromagnetic pinch is a unique phenomenon in the tundish with channel type induction heater. To have a deep insight into the electromagnetic pinch effect, numerical simulation is applied to investigate the magnetohydrodynamic flow in the tundish. Research results show that the magnetic field, flow field, and temperature field predicted by the mathematical model agree well with the experimental data. Induced current density, magnetic flux density, electromagnetic force, and Joule heat in two channels are symmetrically distributed and are greater than that in the receiving and distributing chambers. The eccentric electromagnetic force leads to the single‐/double‐recirculation zones in the channel. There are larger separation areas in the channel enclosed with the iron core than in the other channel, and it is easy for molten steel to separate from the channel wall surface at the top of the channel. Different forces play different roles in the pinch condition, and the order of importance is as follows: electromagnetic force, stress, gravity, supporting force, centrifugal force, and thermal buoyancy. Abstract : Herein, numerical simulation is applied to investigate the magnetohydrodynamic flow in the tundish to have a deep insight into the electromagnetic pinch effect. Different forces play different roles in pinch conditions, and the order of importance is as follows: electromagnetic force, stress, gravity, supporting force, centrifugal force, and thermal buoyancy.